Antimycobacterial anthraquinone-chromanone compound and diketopiperazine alkaloid from the fungus Chaetomium globosum KMITL-N0802 - Kanokmedhakul, Somdej; Kanokmedhakul, Kwanjai; Phonkerd, Nutchanat; Soytong, Kasem; Kongsaeree, Palangpon; Suksamrarn, Apichart (My University, 2002)
Investigation of the fungus Chaetomium globosum KMITL-N0802 led to the isolation of a novel anthraquinone-chromanone compound named chaetomanone along with seven known compounds, ergosterol, ergosteryl palmitate, chrysophanol, chaetoglobosin C, alternariol monomethyl ether, echinuline and isochaetoglobosin D. These compounds were characterized by spectroscopic methods. Chaetomanone and echinulin exhibited activity towards Mycobacterium tuberculosis.